1982
DOI: 10.1016/0014-5793(82)80200-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure at restriction endonuclease MboI cleavage sites protected by actinomycin D or distamycin A

Abstract: Restriction endonucleaseMboI cleavage of DNA was inhibited by actinomycin D and distamycin A. The two inhibitors protected different subsets of the 8 cleavage sites in polyoma DNA. The cleavage reactions were analyzed both in the presence of minimal inhibitory concentrations of the compounds and at higher concentrations, allowing cleavage at only 1 site/DNA molecule. The experiments showed that cleavage sites most efficiently protected by actinomycin D had putative inhibitor binding sites at a distance of 1-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The other cleavage sites are poorly protected by distamycin. This is in agreement with the findings of Nilsson et al (1982) who showed that the most protected cleavage sites of MboI have distamycin binding sites within 2 bp of, or immediately adjacent to, the enzyme's recognition sequence, whereas less protected sites have distamycin binding sequences 4-7 bp away. One can speculate that the slight difference in distamycin concentrations necessary to inhibit the enzyme activity of NruI and AviII results from differences of their flanking sequences and that the inhibition of the enzyme-catalysed cleavage reaction is caused by an alteration of the conformation at and around the recognition site by distamycin.…”
Section: Resultssupporting
confidence: 93%
“…The other cleavage sites are poorly protected by distamycin. This is in agreement with the findings of Nilsson et al (1982) who showed that the most protected cleavage sites of MboI have distamycin binding sites within 2 bp of, or immediately adjacent to, the enzyme's recognition sequence, whereas less protected sites have distamycin binding sequences 4-7 bp away. One can speculate that the slight difference in distamycin concentrations necessary to inhibit the enzyme activity of NruI and AviII results from differences of their flanking sequences and that the inhibition of the enzyme-catalysed cleavage reaction is caused by an alteration of the conformation at and around the recognition site by distamycin.…”
Section: Resultssupporting
confidence: 93%